Sosialisasi Konsep Pertanian Modern di MA Nizhamiyah Ploso Sebagai Upaya Regenerasi Petani - Hariri, Rif'an (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Ploso sub-district is part of the Jombang district, which has potential in the agricultural sector. Currently, in the Ploso sub-district, there is a problem in the form of slowing farmer regeneration. The younger generation is not very interested in the agricultural sector. This phenomenon can be seen from the number of farmer household heads in Ploso Sub-district, which is the lowest in Jombang District. This needs to be done to increase the interest of the younger generation in the agricultural sector. The methods used in this community service are presentations and direct interviews. The results obtained show that most students at MA Nizhamiyah Ploso hold the view that agriculture is limited to planting crops on land. After socialization, the majority of students are of the view that the agricultural sector can also generate profits if managed properly. They also have an interest in the farming sector